Employer monopsony power in the labor market for undocumented workers - Julie L. Hotchkiss; Myriam Quispe-Agnoli (Federal Reserve Bank of Atlanta, 2012)
Using matched employer-employee data from the state of Georgia, this paper investigates how differences in wage responsiveness contribute to the determination of observed wage differentials between documented and undocumented workers. Facing fewer employment opportunities, undocumented workers are found to be about 22 percent less sensitive than documented workers to employers' wage adjustments. In addition, this difference in wage responsiveness accounts for 27 percent of the observed within-firm wage differential between documented and undocumented workers. Implications of the results for recent state immigration legislation are discussed.
Keywords: J42; J61; J2; 330; labor demand; monopsony; illegal immigration; undocumented workers